IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR SISWA - Mustika Fitri Larasati Sibuea (Universitas Islam Sumatera Utara, 2017)
Abstract. The purpose of this study is to know whether the cooperative learning model type Think Talk Write (TTW) can improve student learning outcomes on the material of Two Variable Linear Equation System in class VIII SMP Swasta Tamansiswa Sukadamai Asahan District. This research is a Classroom Action Research. Subjects in this study are students of class VIII SMP Swasta Tamansiswa Sukadamai Asahan regency as many as 36 students. The object of this research is the use of cooperative learning model type Think Talk Write (TTW) in improving student learning outcomes. The instrument used in this study is the test of learning outcomes in the form of test essays and observation sheets. The results obtained before the given learning there are 30.6% of students who have completed, after given the learning in the first cycle there are 63.9% of students who have completed and increased after learning on cycle II there are 86.1% of students who have completed study With absorption capacity of 65%.Keywords: cooperative learning model type Think Talk Write (TTW), learning outcomesAbstrak. Tujuan penelitian ini adalah untuk mengetahui apakah model pembelajaran kooperatif tipe Think Talk Write (TTW) dapat meningkatkan hasil belajar siswa pada materi Sistem Persamaan Linear Dua Variabel di kelas VIII SMP Swasta Tamansiswa Sukadamai Kabupaten Asahan. Penelitian ini merupakan Penelitian Tindakan Kelas. Subjek dalam penelitian ini adalah siswa kelas VIII SMP Swasta Tamansiswa Sukadamai Kabupaten Asahan sebanyak 36 siswa. Objek dalam penelitian ini adalah penggunaan model pembelajaran kooperatif tipe Think Talk Write (TTW) dalam meningkatkan hasil belajar siswa. Instrumen yang digunakan dalam penelitian ini adalah tes hasil belajar dalam bentuk essay tes dan lembar observasi. Hasil penelitian diperoleh sebelum diberikan pembelajaran terdapat 30,6% siswa yang telah tuntas, setelah diberikan pembelajaran pada siklus I terdapat 63,9 % siswa yang telah tuntas dan mengalami peningkatan setelah dilakukan pembelajaran pada siklus II terdapat 86,1% siswa yang telah tuntas belajar dengan daya serap 65%.Kata Kunci: Kooperatif Think Talk Write (TTW), Hasil Belajar Siswa.